Inclusive educational leadership to establish a co-operative school cluster trust? Exploring perspectives and making links with leadership for learning. Issue 11 (2nd November 2019) - Swaffield, Sue; Major, Louis
ABSTRACT: One remarkable feature of the contemporary school landscape in England is the number of schools that have chosen the co-operative framework to shape their work and relationships. When a group of schools decides to become a co-operative trust,  leadership challenges arise both in the process of establishing an inclusive collaborative cluster and in living out co-operative values. To add to the limited literature on co-operative school leadership, a study in a school cluster trust explored headteachers', governors' and teachers' perspectives and beliefs through interviews, group discussions and questionnaires. These data sources revealed some of the motivations for, benefits of, and strategies to support inter-school collaboration guided by the co-operative values of democracy, solidarity, equality, equity, self-help and self-responsibility. Importantly, a range of perspectives on the extent to which leadership was viewed as, and appeared to be, an inclusive practice undertaken by all members of the cluster was identified. A particular contribution of this work is that it exemplifies resonances between the values and principles of the co-operative movement and those of the Leadership for Learning framework. Since these two models are being increasingly adopted and integrated into a variety of educational settings, the research findings may inform leadership practice more widely.